PENGARUH GOOD GOVERNANCE TERHADAP PENGENTASAN KEMISKINAN DI PROPINSI PAPUA BARAT DALAM PERSPEKTIF EKONOMI KELEMBAGAAN BARU - , Kostantinus Edward Jenner Renjaan, SE., Prof. Dr. Wihana Kirana Jaya, M.Soc.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Good governance and poverty alleviation were closely related because the good governance could influence the poverty level through the quality of the public services delivered by a government regime. The difference between successful economy and unsuccessful economy was found in the government institutional policies or infrastructures that supported economic activities. Good infrastructures would support production and the production subsequently supported the economic activities. The difference between rich country institutions and poor country institutions also played an important role. It was because the government institutions were the ones that created both formal and informal rules. The high level of the poverty in West Papua province took place because of the lack of the good governance with the main variables of low participation of people in public policy making (i.e., voice and accountability), the low quality of public services, bureaucracy, bureaucratic independence, and government credibility in the implementation of the policies (i.e., government effectiveness), the lack of public policies that created conducive business climate (i.e., regulatory quality) and the weak law enforcement (i.e., rule of law). The study aimed at analyzing how significant was the impact of the good governance variables on the poverty level of West Papua province. The dependent variable of the study was poverty level, while the independent variables were voice and accountability, government effectiveness, regulatory quality and rule of law. Econometric method was used to analyze the impact of the good governance on the alleviation of the poverty in West Papua province in the perspective of new institutional economy using logistic binary regression analysis. The appropriateness of the studyâs model was measured using Chi square value with Hosmer and Lemeshowâs goodness of fit test. The results of the estimation using the logistic binary method showed that there were three variables that had significant impact on the probability of the poverty level in Wes Papua province. The three variables were voice and accountability, regulatory quality and rule of law, while the variable of government effectiveness did not have any significant impact.